Implementasi Peran Guru dalam Menumbuhkan Budaya Akademik Peserta Didik di Madrasah Aliyah Hidayatul Mubtadiin Sidoharjo Kecamatan Jati Agung Lampung Selatan - Bela Amelia; Etika Pujianti; Nur Widiastuti (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
The main objective of this study is to analyze the implementation of teachers' roles in fostering students' academic culture at Madrasah Aliyah Hidayatul Mubtadiin Sidoharjo, with a focus on strengthening religious values, learning discipline, and active student participation in the academic environment. This study uses a descriptive qualitative approach to analyze the implementation of teachers' roles in fostering students' academic culture at Madrasah Aliyah Hidayatul Mubtadiin Sidoharjo. The research subjects included teachers and students selected through purposive sampling. Data were collected through participant observation, in-depth interviews, and document review. Data analysis was conducted inductively through data reduction, presentation, and verification stages with triangulation and member checking to ensure the credibility of the research findings. The results of this study indicate that the implementation of teachers' roles at Madrasah Aliyah Hidayatul Mubtadiin contributes significantly to building students' academic culture holistically. Teachers serve as academic and religious role models who not only transfer knowledge but also instill the values ??of honesty, discipline, responsibility, and Islamic ethics in the learning process. A clear learning structure through regular scheduling, academic achievement targets, and regular evaluations has been shown to encourage student discipline and independence in learning. Furthermore, active student engagement in discussions, academic projects, and learning support activities strengthens a collaborative and participatory academic culture. These findings confirm that quality teacher-student interactions, systematic learning, and active student participation are key factors in creating a sustainable academic environment and developing students who are intelligent, have character, and are morally upright.